Emily Windsnap and the monster from the deep / 2. - Kessler, Liz (Emily Windsnap, 2006)
Reunited with her merman father and now living on an island located in the Bermuda Triangle, twelve-year-old Emily accidentally awakens the fearsome kraken and also faces a bully from her past.